Inulin Content in Chipped Roots of Cardoon Stored at Different Initial Moisture Contents After Six-Month Storage - Alfano, Vincenzo; Stefanoni, Walter; Latterini, Francesco; Liuzzi, Federico; De Bari, Isabella; Viola, Egidio; Ciancolini, Anna; Pari, Luigi (Frontiers in Energy Research, 2022)
Inulin is accumulated as a reserve carbohydrate in the roots and tubers of many plants belonging to the Asteraceae family. At present, most of the inulin for nutraceutical purposes is produced from Jerusalem artichoke (Helianthus tuberosus L.) and Chicory (Cichorium intybus L.), but also cardoon is proved to synthetize and store high quantity of inulin in roots. Inulin in the roots of cardoon reaches the maximum content before the beginning of flowers formation in May. Due to the limited favorable period for harvesting the roots, storage plays a key role in supply chain. The complete drying of cardoon roots before the storage has been proved to prevent the degradation of inulin up to six months of storage. Since drying is a costly operation, in the present study the energy saving and the effect on percentage inulin content in cardoon roots dried at different moisture content before storage was assessed. From 48.2% inulin retrievable at beginning of the investigated period (100% dry matter), after one month of storage, about 2% reduction was recorded on average in H0 and H12.5 treatments, while about 10% reduction was shown (with no statistical differences) in treatments at higher moisture content (TQ, H50 and H25). These values remained constant until the end of storage, except for TQ treatment, where inulin content decreased progressively up to 38.7 % w/w. From economic point of view, limiting the drying time and storing roots at a moisture content higher than 0% leads to an income loss of 2000-3000 €/t of roots. Therefore, full drying is the most cost-effective solution in the optic of producing the highest possible amount on inulin and could be avoided just in the case of immediate roots extraction and processing in a few days.